O arconte e o seu outro : Gabriel García Márquez e os mcondistas - Costa, Sérgio Luiz de Souza (2007)
This Dissertation maps, from a comparative perspective, the works of Gabriel García Márquez, Alberto Fuguet, and Edmundo Paz Soldán as authors with distinct perceptions of Latin America. These authors literary production has been investigated as inscribing distinct realities and perceived as representing imaginary cartographies and ancestral memories. The notion of the archive, as conceived by Michel Foucault and Jacques Derrida, has been used as a theoretical framework, placing Garcia Marquez as the Archon, i.e., the gatekeeper of the archives of Latin American culture. Accordingly, concepts of time and space, intertwined with a keen sense of power relations, have been deployed as the main analytical tools. The context of late modernity, and the logic that exceeds it, has been confirmed as an important framework for the analysis undertaken